Pembelajaran Pendidikan Agama Islam Ranah Afektif Mata Pelajaran Akidah Akhlak Di Madrasah Ibtidaiyah Amanah Ummah Masaran - Muhammad Ilyas; Achmad Rasyid Ridha (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
Faith (Aqidah) and morality (Akhlaq) are the essence of Islamic law (Shari'a). Aqidah is the foundation and basis of faith, while Akhlaq is the manifestation of faith in behavior or righteous deeds. Noble character was the primary mission of the Prophet Muhammad. In several verses of the Quran, faith and righteous deeds are often mentioned together. The main challenge in development is human development (human resource development), alongside natural resource development. High-quality human resources are not solely characterized by intelligence and skills; equally important are attitudes and mental disposition. The demand for the development of an evaluation system is increasingly strong in the group of subjects related to Religious Education and Noble Character (without disregarding the importance of other subject groups). This article aims to examine the extent to which the implementation of affective domain evaluation in Aqidah Akhlaq learning at MI Amanah Ummah Masaran applies the affective domain to measure students' attitudes towards Aqidah Akhlaq subjects based on affective domains. Abstrak Akidah dan akhlak merupakan substansi syariat Islam. Akidah merupakan fondasi dan dasar-dasar keimanan, Akhlak merupakan manifestasi keimanan dalam perilaku atau amal shalih. Akhlak yang mulia adalah misi utama Rasulullah. Iman dan amal salih dalam sejumlah ayat dalam Al Quran sering dikemukakan secara beriringan. Tantangan pembangunan yang utama adalah pembangunan manusia (pengembangan sumber daya manusia) di samping sumber daya alam. SDM yang berkualitas tidak semata-mata dalam bentuk dimilikinya kecerdasan dan keterampilan melainkan yang tidak kalah pentingnya adalah sikap dan mental. Tuntutan pengembangan sistem evaluasi semakin menguat pada kelompok mata pelajaran Pendidikan Agama dan Akhlak Mulia (tidak berarti pada kelompok mata pelajaran yang lain tidak ditekankan). Artikel ini bertujun untuk melihat sejauh mana Implementasi evaluasi ranah afektif dalam pembelajaran akidah akhlak di MI Amanah Ummah Masaran adalah menerapkan domain ranah afektif untuk mengukur sikap siswa terhadap mata pelajaran akidah akhlak yang didasarkan pada domain-domain afektif.